Influence of Udder Morphological Traits on Milk Parameters in Healthy Sahiwal and Crossbred Cattle - Maiti, Abhinaba; Huozha, Ruokuobeinuo; Thakur, Swati; Patel, Mayank; Salaria, Ameeta; Ambwani, Tanuj; Kumar, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Ten each healthy lactating Sahiwal and crossbred cows were selected from the University Instructional Dairy Farm. Milk samples was collected without any preservative from lactation stage; early (30-90±15 days), mid (100-180±15 days) and late (200-280±15 days) and analysed for milk composition using Ultrascan milch analyser, enumeration of somatic cell and differential leucocyte counts by modified May-Grünwald and Giemsa staining techniques. Udder morphological traits of mammary teat shape (cylindrical, conical, bottle) and udder shape (round, bowl, trough) were done before milking. Test day milk yield was recorded highest in round shaped followed by bowl and least in trough udder shape. Round udder and cylindrical teat shape had significantly (p<0.05) higher milk somatic cell count and least in trough udder and conical teat shape. Cylindrical teat shape had significantly (p<0.05) higher milk neutrophil % in both cattle, while higher milk lymphocyte % in bottle teat shape of Sahiwal and conical teat shape of crossbred cows. Significant (p<0.05, p<0.01) positive correlations were observed between udder circumference, width, depth and teat apex, mid diameter with milk SCC; udder circumference, width, depth and teat length, apex, mid, base with milk neutrophil; udder height from the ground with milk lymphocyte in crossbred cattle. In Sahiwal cattle, significant positive correlations were noted only between udder circumference, depth and teat base with milk SCC. It is concluded that udder morphology has a significant impact on protection of mammary gland against intra-mammary infections and maintain udder health in lactating dairy cows.